2015
DOI: 10.1080/17441692.2015.1076019
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to health-care access: A qualitative study among African migrants in Guangzhou, China

Abstract: Guangzhou is China's third most populous city, and the region's burgeoning manufacturing economy has attracted many young African businessmen and entrepreneurs to the city. The aims of this study were to examine strategies that African migrants in Guangzhou have adopted in response to health care barriers, and explore their perceptions of how to address their needs. Twenty-five semi-structured interviews and two focus groups were conducted among African migrants residing in Guangzhou, China. Facing multiple ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In addition, there have been a few projects aimed at understanding African immigrant health in other countries. Those studies revealed a number of barriers to African immigrants' healthcare access that were similar to U.S. studies [31][32][33]. For instance, African immigrants in other countries, like in the U.S., were found to be often viewed as a part of a larger homogeneous population [34][35][36].…”
Section: Introductionmentioning
confidence: 75%
“…In addition, there have been a few projects aimed at understanding African immigrant health in other countries. Those studies revealed a number of barriers to African immigrants' healthcare access that were similar to U.S. studies [31][32][33]. For instance, African immigrants in other countries, like in the U.S., were found to be often viewed as a part of a larger homogeneous population [34][35][36].…”
Section: Introductionmentioning
confidence: 75%
“…The only immigrant subgroups that have been studied are the African immigrants in Guangzhou, where there are now at least 20,000 legal African residents, and an unknown number of illegal residents residing in the city, making Guangzhou home to Asia’s largest African migrant population [ 13 , 14 ]. Based on an in-depth qualitative study, scholars have found that African immigrants in Guangzhou experienced various barriers to accessing health care and were generally dissatisfied with local health services [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Personal financial funds are needed to access both private care and health insurance. Lack of health insurance can have a significant negative impact on access to care in many countries [ 5 , 6 ]. If insurance has been paid, the Romanian system can offer some benefits of universal healthcare coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination through stereotyping is also prevalent with Roma being judged by healthcare staff based on their education and unemployment rates causing mistrust toward professionals [ 6 , 10 , 21 ]. Negative experiences from mistreatment or prejudice result in reluctance to attend services and negatively impacts perception of health [ 5 , 21 , 22 ]. Cultural barriers also have a strong relationship with community willingness to access appropriate care [ 23 ].…”
Section: Introductionmentioning
confidence: 99%